DISTRIBUTION AND GENETIC RESOURCE OF MONGOLIAN NATURAL WILD SEABUCKTHORN /HIPPOPHAE.RH/ (Mongolian Journal of Agricultural Sciences, 2015)
Mongolian natural wild seabuckthorn covers 13.5 thousand hectare along six river basins of six aimags (Selenge, Bulgan, Zavkhan, Govi-Altai, Khovd and Uvs), respectively. Within the frame of the study 43 forms were selected by morphology-biological peculiarity and 21 forms were determined as selection’s basic material and genetically important material and stored in the gene pool of agricultural cultivars. To see the chemical composition of natural cultivars, the samples had medium sugar, low fat and medium vitamin C content. 50-86.7% of all bushes and trees have age of over 10 years, 13-50% have 10-18 years age, this shows tree and bushes are relatively young.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 55-59